Uji Aktivitas Beberapa Subfraksi Etil Asetat dari Herba Meniran (Phyllanthus niruri Linn.) Terhadap Reaksi Hipersensitivitas Kutan Aktif - Aldi, Yufri; Mahyudin, Mahyudin; Handayani, Dian (Fakultas Farmasi Universitas Andalas, 2013)
A study on the activity of some ethyl acetate subfraction of meniran herbs (Phyllanthus niruri Linn.) on the cutaneous active hypersensitive reaction has been conducted. The subfraction (1,2, and 3) were at the dose of 50 mg/Kg BW and 100 mg/Kg BW dispersed with 1% tween 80: Chicken egg albumin at concentration 25% and 30% were used as control, all of which were given for 10 days. The Hipersensitivity reaction was observed at day 10th. Result Showed that subfraction 1,2, and 3 at doses 50 mg/Kg BW and 100 mg/Kg BW inhibited hypersensitivity, reaction significantly, the onset of blue skin bump were best given by subfraction 3 (dose 100 mg/Kg BW), the diameter of blue skin bump were best given by subfraction 2 (50 mg/Kg BW) and the intensity of the blue skin bump was besy given by subfraction 2 (100 mh/Kg BW). In summary, the ethyl aceble subfraction of meniron herbs (Phyllanthus niruri Linn.) showed an immunostimulan activity